2006
DOI: 10.1038/sj.bjc.6603287
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of docetaxel and mitoxantrone for the treatment of metastatic hormone-refractory prostate cancer

Abstract: A systematic review was performed to evaluate the clinical effectiveness of docetaxel in combination with prednisolone (docetaxel is licensed in the UK for use in combination with prednisone or prednisolone for the treatment of patients with metastatic hormonerefractory prostate cancer. Prednisone is not used in the UK, but it is reasonable to use docetaxel plus prednisone data in this review of docetaxel plus prednisolone) for the treatment of metastatic hormone-refractory prostate cancer. A scoping search id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In addition, the type II topoisomerase inhibitor mitoxantrone, which is widely used for the treatment of various tumor types, was recently identified as an USP11 inhibitor. Although mitoxantrone involves various pathways, such as inhibition of topoisomerase and induction of immunogenic cell death, to suppress tumor growth, [45][46][47] our data suggest that inhibition of the USP11-cIAP2 pathway by mitoxantrone contributes to its anticancer effects. Thus, combination treatment with mitoxantrone and Smac mimetics and/or TRAIL may synergistically enhance the desired antitumor effects.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, the type II topoisomerase inhibitor mitoxantrone, which is widely used for the treatment of various tumor types, was recently identified as an USP11 inhibitor. Although mitoxantrone involves various pathways, such as inhibition of topoisomerase and induction of immunogenic cell death, to suppress tumor growth, [45][46][47] our data suggest that inhibition of the USP11-cIAP2 pathway by mitoxantrone contributes to its anticancer effects. Thus, combination treatment with mitoxantrone and Smac mimetics and/or TRAIL may synergistically enhance the desired antitumor effects.…”
Section: Discussionmentioning
confidence: 77%
“…It has been seen that Doc induces apoptosis through the mitotic catastrophe mechanism in different experimental models [18,19]. In fact, it was previously demonstrated that this taxane induces mitotic catastrophe in PC3 and DU145 lines, triggering the onset and development of a proliferating aneuploid cell population characterized by significantly altered DNA content [15]. In our preclinical model it is reasonable to suppose that the cells damaged by Doc but still proliferating represented a suitable target for the effect of a DNA-damaging agent such as ST1481, with the consequent increase in apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel, which belongs to the family of taxanes, exerts its key mode of therapeutic action through the suppression of microtubule dynamic assembly and disassembly and, thus, the disruption of mitotic cell division, finally leading to apoptosis (Van Poppel, 2005). Mitoxantrone, is an anthracenedione, which through targeting and inhibiting topoisomerase II, impedes DNA and RNA synthesis, produces DNA strand breaks and, ultimately, induces apoptotic phenomena (Boland et al, 2000;Collins et al, 2006). Previous work from our research group has demonstrated that a broad range of chemotherapeutic agents, including anthracenediones and taxanes, cause distinct modulations of apoptosis-related genes, in a variety of human cancer cell lines.…”
Section: Figurementioning
confidence: 97%
“…Several clinical trials have demonstrated that employment of chemotherapeutic compounds docetaxel and mitoxantrone increases the survival of HRPC patients. These data lead to the approval of these regimens for standard HRPC treatment (Berry, 2005;Collins et al, 2006;Lassi and Dawson, 2009). However, it is believed that administration of a proper treatment scheme could only confront the disease temporarily, and thus should be accompanied by accurate tools for monitoring each cancer patient's response to it (Pienta and Smith, 2005;Hadaschik and Gleave, 2007;Lassi and Dawson, 2009).…”
mentioning
confidence: 96%
See 1 more Smart Citation